Multi-stimuli responsive chromism with tailorable mechanochromic sensitivity for versatile interactive sensing under ambient conditions. Issue 1 (21st August 2019) - Zeng, Songshan; Sun, Haotian; Park, Cheonjin; Zhang, Monica; Zhu, Mengting; Yan, Manqing; Chov, Nora; Li, Edward; Smith, Andrew T.; Xu, Gefan; Li, Shuliang; Hou, Zaili; et al.
Abstract : A 3D integration strategy is applied to fabricate multi-stimuli responsive chromic devices that respond to UV, temperature, and mechanical stretching. Abstract : Multi-stimuli responsive (MSR) chromic materials which can exhibit a color change when exposed to external stimuli demonstrate huge potential in developing new intelligent devices. However, they commonly require complicated synthesis processes that are not suitable for mass production. To facilitate the fabrication of MSR devices, for the first time, we propose a facile 3D integration strategy to rationally assemble various commercial chromic materials, light shielding layers, and a stretchable substrate into a set of MSR devices equipped with thermo-/photo-/mechanochromic characteristics with negligible cross-interferences. Notably, the mechanochromic sensitivity can be readily adjusted to multiple levels via facile pre-stretching methods. Moreover, two types of MSR units are integrated into an interactive electronic device, which exhibits thermo-/photo-/electrochromic responses, and two levels of mechanochromic responses with color changes at 100% and 200% strain, respectively. In addition, another highly sensitive MSR unit is applied to a wearable motion/environmental monitoring chromic device, which can detect finger bending within 30% strain, and monitor environmental stimuli (UV, temperature) with thermal mapping capability. A smartphone-based colorimetric analysis app was also developed for finger bending detection. Comprehensive quantitative characterization and finite element analysis are used to elucidate the performance and intrinsic mechanisms of these MSR responses.